’Ma mère l’oye’ and the misfortunes of the musical canon - Giani, Maurizio (Musica Docta, 2014)
This essay introduces and discusses a series of viewpoints on the Western musical canon, selected from the most representative of those that can be found on the web. The focus is almost exclusively on Italian websites, from Wikipedia entries to various forums. I have deliberately given more room to statements of modest cultural and intellectual value, for their documentary value as evidence of widespread opinions, and real attitudes, that give us a vivid picture of how serious the situation is. One of the worrying aspects in this survey of mostly negative judgments is the fact that, among these boorish critics of the Musical Canon, there are also esteemed musicologists, who seem to enthusiastically support the primitivism of so many immature critics of “classical stuff”, mimicking their jargon and hostility towards highbrow culture. Their purpose in doing so may be to ingratiate themselves with their dialogue partners, but it is unclear whether, after successfully applying this ‘entryist’ tactic, they intend to carry out targeted educational actions (a sort of modern take on Horace’s castigare ridendo mores, or correcting customs by laughing at them) – or whether, as seems more likely, they just want to climb on the bandwagon.